Diferencias y semejanzas entre la extorsión y el abuso de la confianza en la legislación Ecuatoriana. - Ayala Sánchez, Mónica Gabriela (2018)
The present investigation deals with the crimes of extortion and abuse of trust, with the purpose of verifying if there is a difference or similarities between these two crimes, as well as their procedural treatment, being two crimes that cause social alarm in the first case. It is carried out using intimidation or violence, meanwhile, in the second case, the primary thing is that the victim trusts the active subject of the crime, that is why it is used. The crime of extortion is analyzed, a legal, doctrinaire and critical analysis of extortion will be carried out, the constitutive elements of the crime of extortion will be verified, the possible psychological consequences of extortion victims, the crime of abuse of trust, elements of the abuse of trust, the similarities and differences between extortion and the abuse of trust. The present research work will be of great importance as a source of consultation for students of the National University of Chimborazo, lawyers in the free exercise of the profession, judges, prosecutors, in order for all citizens in general and in this way have knowledge about the crimes of extortion and the abuse of trust.